Perceptually Correlated Parameters of Musical Instrument Tones - BEAUCHAMP, James W. (Archives of Acoustics, 2011)
In Western music culture instruments have been developed according to uniqueinstrument acoustical features based on types of excitation, resonance, and radiation.These include the woodwind, brass, bowed and plucked string, and percussionfamilies of instruments. On the other hand, instrument performance depends onmusical training, and music listening depends on perception of instrument output.Since musical signals are easier to understand in the frequency domain than the timedomain, much effort has been made to perform spectral analysis and extract salientparameters, such as spectral centroids, in order to create simplified synthesis modelsfor musical instrument sound synthesis. Moreover, perceptual tests have been madeto determine the relative importance of various parameters, such as spectral centroidvariation, spectral incoherence, and spectral irregularity. It turns out that theimportance of particular parameters depends on both their strengths within musicalsounds as well as the robustness of their effect on perception. Methods that the authorand his colleagues have used to explore timbre perception are: 1) discriminationof parameter reduction or elimination; 2) dissimilarity judgments together with multidimensionalscaling; 3) informal listening to sound morphing examples. This paperdiscusses ramifications of this work for sound synthesis and timbre transposition.